2011
DOI: 10.4018/jmbl.2011100102
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Mobile Game-Based Learning

Abstract: This paper investigates whether there are gender differences in gameplay time and learning outcomes in a social studies mobile game-based curriculum. Seventeen boys and 24 girls from a ninth-grade class in Singapore used a mobile learning game Statecraft X to enact governorship in the game world. The data suggest that boys spent significantly more time playing Statecraft X than girls. However, there were no significant gender differences in their scores in an essay question assessing their learning about gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Counter-intuitively, no significant gender differences in their scores materialized (Tan et al 2011). The finding of Tan et al's (2011) research concluded that more time spent on game play did not correlate with learning outcomes statistically (Tan et al, 2011). The quasi-experimental research of DGBL in classroom-based science education for elementary levels found that not only did both gender groups consistently have better engagement, but DGBL also positively impacted upon content knowledge on science topics and on problem-solving skills (Lester et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…Counter-intuitively, no significant gender differences in their scores materialized (Tan et al 2011). The finding of Tan et al's (2011) research concluded that more time spent on game play did not correlate with learning outcomes statistically (Tan et al, 2011). The quasi-experimental research of DGBL in classroom-based science education for elementary levels found that not only did both gender groups consistently have better engagement, but DGBL also positively impacted upon content knowledge on science topics and on problem-solving skills (Lester et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Another study with 17 boys and 24 girls at a secondary school in Singapore, using a mobile learning game named 'Statecraft X' to enact governorship, found males spent significantly more time playing than females (Tan, Chee, & Gwee, 2011). Counter-intuitively, no significant gender differences in their scores materialized (Tan et al 2011). The finding of Tan et al's (2011) research concluded that more time spent on game play did not correlate with learning outcomes statistically (Tan et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, there are many contributions on m-learning, considering it only from a purely technological perspective [6][7][8], it is important to study it from a socio-cultural ecological approach [1]. This approach considers that it is necessary to explore m-learning from different areas: educational, social, cultural, media, technological and semiotic.…”
Section: Proceedingsmentioning
confidence: 99%
“…The use of educational games in the classroom is commonly done with desktops, laptops, mobiles, augmented reality, interactive tables and tablets Goh, Shou, Tan, & Lum, 2012;Gwee, San Chee, & Tan, 2011). An alternative is the Interpersonal Computer with shared display, which allows all students in a course to interact simultaneously while the teacher can monitor the students' work to mediate those in need (Alcoholado et al, 2012).…”
Section: Introductionmentioning
confidence: 99%